2018
DOI: 10.1055/s-0044-100037
|View full text |Cite
|
Sign up to set email alerts
|

Praktikabilität und Leistungsfähigkeit von E-Health-Anwendungen bei der Erhebung von Patient Reported Outcomes: Forschungsstand und -bedarf

Abstract: The standards of the legislators must be specified and adapted to the requirements of ePRO. Because the design of the tool surface and the rate of usability can influence the response behavior of the patients, the focus should be on the reliability and validity of ePRO surveys in the context of their implementation in relation to the patients, disease, questionnaire and ePRO-specific variables, which determine the response behavior, in order not to endanger the meaningfulness of PRO surveys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Thus, a corresponding analysis in relation to differences and correlations between the paper-based version of FACT-B and newly developed Web-based tools are of great importance. It can be assumed that many aspects (ie, sociodemographic aspects, technical skills, health condition, and, perhaps, design specifics of the ePRO tool) may influence both patients’ willingness to use the tool and their response behavior, which underlines the need for reliability analyses [10,24,35-37]. However, almost no scientific studies have dealt with the reliability of ePRO questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a corresponding analysis in relation to differences and correlations between the paper-based version of FACT-B and newly developed Web-based tools are of great importance. It can be assumed that many aspects (ie, sociodemographic aspects, technical skills, health condition, and, perhaps, design specifics of the ePRO tool) may influence both patients’ willingness to use the tool and their response behavior, which underlines the need for reliability analyses [10,24,35-37]. However, almost no scientific studies have dealt with the reliability of ePRO questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…Although paper-based surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated the feasibility and acceptance of HRQoL in the ePRO measurement in the last few years [29-34]. Nevertheless, knowledge regarding patients’ acceptance, feasibility, and barriers remains limited [35], especially because hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37]. Although studies have already demonstrated a potential equivalence between some paper-based PRO and ePRO, the reliability of ePRO questionnaires should be verified so as not to endanger the validity of ePRO surveys [10,36-40].…”
Section: Introductionmentioning
confidence: 99%
“…Although paperbased surveys of PRO still predominate because there are only a few reliable and validated ePRO questionnaires, numerous projects have evaluated feasibility and acceptance of HRQoL in ePRO measurement in the last few years [29][30][31][32][33][34]. Nevertheless, knowledge regarding patient acceptance, feasibility, and barriers remains limited [35], especially since hurdles might exist in relation to health status, technical skills, and socioeconomic aspects, which could influence both patients´ willingness to use ePRO and their response behavior [10,36,37]. Although studies have already demonstrated a potential equivalence between some paper-based PRO and ePRO, reliability of ePRO questionnaires should be verified so as not to endanger the validity of ePRO surveys [10,[36][37][38][39][40].…”
Section: Electronic Measurement Of Patient-reported Outcomesmentioning
confidence: 99%
“…Thus, a corresponding analysis in relation to differences and correlations between the paper-based vision of FACT-B and newly developed online tools are of great importance. It can be assumed that many aspects (i.e., sociodemographic aspects, technical skills, health condition, and perhaps design specifics of the ePRO tool) may influence both patients' willingness to use the tool and their response behavior, which underlines the need for reliability analyses [10,24,[35][36][37]. However, almost no scientific studies have dealt with the reliability of ePRO questionnaires.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…In recent years an emphasis has been made on patient-reported outcomes (PRO) as a means of collecting HRQoL data. PROs are characterized by the fact that several validated questionnaires are used simultaneously for HRQoL measurement in order to balance the respective subjectivity [8].…”
Section: Introductionmentioning
confidence: 99%